2020
DOI: 10.3389/fimmu.2020.590870
|View full text |Cite
|
Sign up to set email alerts
|

The Neat Dance of COVID-19: NEAT1, DANCR, and Co-Modulated Cholinergic RNAs Link to Inflammation

Abstract: The COVID-19 pandemic exerts inflammation-related parasympathetic complications and post-infection manifestations with major inter-individual variability. To seek the corresponding transcriptomic origins for the impact of COVID-19 infection and its aftermath consequences, we sought the relevance of long and short non-coding RNAs (ncRNAs) for susceptibility to COVID-19 infection. We selected inflammation-prone men and women of diverse ages among the cohort of Genome Tissue expression (GTEx) by mining RNA-seq da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 163 publications
(157 reference statements)
2
43
0
Order By: Relevance
“…These results reveal the role of lncRNAs in innate immunity and suggest that NEAT1 is a common mediator of inflammatory signaling induction. Furthermore, Chanan Meydan et al showed that sharp declines in the lung pathology-associated lncRNA DANCR and the nuclear paraspeckles forming the neuroprotective lncRNA NEAT1 are potentially associated with the susceptibility to and outcome of COVID-19 infection (46). The inflammationmodulating lncRNA DANCR, as a potential chief regulator, is responsible for the surveillance of inflammatory cholinergic blockade, thus supporting the maintenance of a delicate balance between pro-inflammatory and anti-inflammatory pathways in SARS-CoV-2-affected lung and brain tissues.…”
Section: Inflammatory Responsementioning
confidence: 99%
See 2 more Smart Citations
“…These results reveal the role of lncRNAs in innate immunity and suggest that NEAT1 is a common mediator of inflammatory signaling induction. Furthermore, Chanan Meydan et al showed that sharp declines in the lung pathology-associated lncRNA DANCR and the nuclear paraspeckles forming the neuroprotective lncRNA NEAT1 are potentially associated with the susceptibility to and outcome of COVID-19 infection (46). The inflammationmodulating lncRNA DANCR, as a potential chief regulator, is responsible for the surveillance of inflammatory cholinergic blockade, thus supporting the maintenance of a delicate balance between pro-inflammatory and anti-inflammatory pathways in SARS-CoV-2-affected lung and brain tissues.…”
Section: Inflammatory Responsementioning
confidence: 99%
“…This research provides arguments to consider that ncRNA-mRNA network. The interconnectivity of this network may be elucidated upon examining shared components such as miR-135b-5p, miR-656-3p, and miR-19a-3p, as some may interact with key relevant downstream mediators such as TNF and IL-6 to affect inflammation, leading to COVID-19 ( 46 ).…”
Section: Potential Mechanisms Of Lncrnas In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“… 40 , 41 The miR-576-3p has been reported to induce interferon production, and gene therapy to restore interferon production may improve prognosis after ischemic stroke. 42 , 43 The miR-665 is down-regulated in T2DM patients and up-regulated in stroke patients. 44 , 45 This suggests that the four miRNAs that we identified – especially miR-576-3p, with the most target genes – may be risk factors and markers for the development of ischemic stroke in T2DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted May 18, 2021. ; https://doi.org/10.1101/2021.05.13.21257152 doi: medRxiv preprint immune dysfunction (14)(15)(16)(17), there are limited studies on the respiratory epithelia specific lncRNAs and their role in SARS-CoV-2 infection (18,19). As such, in this study, we assessed acute mucoinflammatory and immunomodulatory responses, including lncRNA expressions in a 3D airway tissue model of acute SARS-CoV-2 infection and COVID-19 patient nasopharyngeal samples to gain novel insights into early innate responses of human respiratory cells.…”
Section: Introductionmentioning
confidence: 99%